2019
DOI: 10.1002/ejhf.1465
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world treatment patterns of sacubitril/valsartan: a longitudinal cohort study in Germany

Abstract: Aims To analyse real‐world treatment patterns of sacubitril/valsartan (sac/val) using data from a pharmacy database in Germany. Methods and results A retrospective cohort study of 26 191 adult patients (aged ≥ 18 years) in the IMS® longitudinal prescriptions database in Germany who were dispensed sac/val from January 2016 to June 2017 was conducted. The analysis included sac/val dose titration assessed in the 6 months from first sac/val prescription; prescriptions of concomitant cardiovascular medications in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
3
5

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 18 publications
(40 reference statements)
4
62
3
5
Order By: Relevance
“…In the main, observations have been in line with what has been reported in the clinical trial data . However, there has been a lower rate of achievement of the target dose (TD), with the majority of studies reaching TD in less than 50% the patients, including a large cohort in Germany . To our knowledge, only one study to date had reported success in titration to TD in greater than 50% of the cases .…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…In the main, observations have been in line with what has been reported in the clinical trial data . However, there has been a lower rate of achievement of the target dose (TD), with the majority of studies reaching TD in less than 50% the patients, including a large cohort in Germany . To our knowledge, only one study to date had reported success in titration to TD in greater than 50% of the cases .…”
Section: Introductionsupporting
confidence: 84%
“…Some studies have reported rates as low as 17%, and the majority of studies achieved the maximum dose in less than 50% of individuals. 11,15,16 Given that emerging data indicate that the higher doses are associated with superior clinical response, 11,18 close analyses of the impediments to dose titration in the community are warranted in order to provide guidance on how best this agent in this setting. Our data demonstrate that the clinical trial dose of sacubitril-valsartan can be achieved in a significant proportion of the population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that 62% of the patients up-titrated to 49/51 or 97/103 mg bid of sacubitril/valsartan are relevant when compared to registry data, showing only 43% of patients receiving more than 24/26 mg bid of sacubitril/valsartan in an outpatient setting. 16,17 This gap between data from controlled trials and daily practice requires further study, and gives room for future improvement in HF therapy. 18 -20 The results of TRANSITION provide support to continuing the efforts of up-titration after discharge.…”
Section: Discussionmentioning
confidence: 99%
“…9,23 Buna karşın yeni yayımlanan çalışmalarda da çalışmamızda olduğu gibi hastalarda sakubitril/valsartan tedavisi sonrasında diüretik ihtiyacında azalma olduğu görülmüştür. [23][24][25] Sakubitril, BNP'yi yıkan ve bir anjiyotensin reseptör nötral endopeptidaz olan neprilisini inhibe ederek kandaki natriüretik peptid seviyelerini artırmaktadır. 26 Yeni yayımlanan çalışmaların sonuçlarına göre sakubitril/valsartan tedavisi atriyal natriüretik seviyesini artırırken, NT-pro BNP seviyesini çalışmamızda olduğu gibi azaltmıştır.…”
Section: Discussionunclassified